Publicity and openness of administrative processes under the Convention on human rights and fundamental freedoms and the European court of human rights - Тацій, Л. В. (Problems of legality, 2013)
This paper attempts to reveal the content of the principles of transparency and openness of administrative litigation with regard to the Convention for the Protection of Human Rights and Fundamental Freedoms. The analysis of the European Court of Human Rights concerning the application of these principles.